Clinical outcomes of multivessel coronary artery disease patients revascularized by robot-assisted vs conventional standard coronary artery bypass graft surgeries in real-world practice. Issue 3 (22nd January 2021) - Lin, Tzu-Hsiang; Wang, Chi-Wei; Shen, Ching-Hui; Chang, Keng-Hao; Lai, Chih-Hung; Liu, Tsun-Jui; Chen, Kuan-Ju; Chen, Yu-Wei; Lee, Wen-Lieng; Su, Chieh-Shou
Abstract : Abstract: The treatment of patients with multivessel coronary artery disease (MVD) by coronary stenting (PCI) and the "gold standard" conventional coronary-artery bypass grafting (C-CABG) has been well explored in the literature. However, the clinical outcomes of robot-assisted CABG (R-CABG) vs C-CABG in MVD patients in real-world practice were unknown. We aimed to study the clinical outcomes of MVD patients who underwent R-CABG (robotic MIDCAB) and C-CABG at our institution between January 2005 and December 2013. A total of 516 MVD patients received CABG were recruited into this study. Among them, 281 patients received R-CABG and 235 patients underwent C-CABG. Patients in the R-CABG group were younger, and had fewer vessels with coronary artery disease (CAD), lower prevalence of chronic renal disease (CKD), higher left ventricular ejection fraction (LVEF), as well as lower Euro scores. The in-hospital and long-term mortalities were lower in the R-CABG group, but the incidences of target lesion revascularization (TLR), target vessel revascularization (TVR), myocardial infarction (MI), and stroke were not significantly different between the two groups. The long-term mortality was related to age, lower LVEF, and CKD, but not residual SYNTAX score, or completeness of revascularization. The revascularization modality (R-CABG vs C-CABG) was a borderline significantly independent predictor of long-term mortality (OR 1.76 [0.99–3.14], P = .055). Our study concluded that R-CABG, in comparison with C-CABG, for MVD carried out in younger patients involved fewer clinical complexities was associated with lower in-hospital and long-term mortalities in real-world practice. However, the long-term rates of TLR, TVR, MI, and stroke were similar. The long-term mortality was correlated with age, lower LVEF, and CKD, where R-CABG remained a borderline significant predictor after correcting for confounding factors. R-CABG could be an effective alternative to C-CABG for MVD patients with fewer clinical complexities in real-world practice.